Ketosis After Intake of Coconut Oil and Caprylic Acid—With and Without Glucose: A Cross-Over Study in Healthy Older Adults - Norgren, Jakob; Sindi, Shireen; Sandebring-Matton, Anna; Kåreholt, Ingemar; Daniilidou, Makrina; Akenine, Ulrika; Nordin, Karin; Rosenborg, Staffan; Ngandu, Tiia; Kivipelto, Miia (Frontiers in Nutrition, 2020)
INTRODUCTION: Medium-chain-triglycerides (MCT), formed by fatty acids with a length of six to twelve carbon atoms (C6-C12), constitute about two thirds of coconut oil (Coc). MCT have specific metabolic properties which has led them to be described as ketogenic even in the absence of carbohydrate restriction. This effect has mainly been demonstrated for caprylic acid (C8), which constitutes about 6-8% of coconut oil. Our aim was to quantify ketosis and blood glucose after intake of Coc and C8, with and without glucose intake. Sunflower oil (Suf) was used as control, expected to not break fasting ketosis, nor induce supply-driven ketosis. METHOD: In a 6-arm cross-over design, 15 healthy volunteers—age 65-73, 53% women—were tested once a week. After a 12-hour fast, ketones were measured during 4 hours after intake of coffee with cream, in combination with each of the intervention arms in a randomized order: 1. Suf (30 g); 2. C8 (20 g) + Suf (10 g); 3. C8 (20 g) + Suf (10 g) + Glucose (50 g); 4. Coc (30 g); 5. Coc (30 g) + Glucose (50 g); 6. C8 (20 g) + Coc (30 g). The primary outcome was absolute blood levels of the ketone β-hydroxybutyrate, area under the curve (AUC). ANOVA for repeated measures was performed to compare arms. RESULTS: β-hydroxybutyrate, AUC/time (mean ±SD), for arms were 1: 0.18 ±0.11; 2: 0.45 ±0.19; 3: 0.28 ±0.12: 4: 0.22 ±0.12; 5: 0.08 ±0.04; 6: 0.45 ±0.20 (mmol/L). Differences were significant (all p≤0.02), except for arm 2 vs. 6, and 4 vs. 1 & 3. Blood glucose was stable in arm 1, 2, 4 & 6, at levels slightly below baseline (p≤0.05) at all timepoints hour 1-4 after intake. CONCLUSIONS: C8 had a higher ketogenic effect than the other components. Coc was not significantly different from Suf, or C8 with glucose. In addition, we report that a 16-hour non-carbohydrate window contributed to a mild ketosis, while blood glucose remained stable. Our results suggest that time-restricted feeding regarding carbohydrates may optimize ketosis from intake of MCT. The study was registered as a clinical trial on ClinicalTrials.gov, NCT03904433.